1999
DOI: 10.1002/(sici)1097-4679(199909)55:9<1095::aid-jclp7>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of short-term treatment at a university counseling center

Abstract: The effectiveness of short‐term treatment provided to 55 students treated at a university counseling center was evaluated. The Symptom Checklist‐90‐R was administered at intake and at the termination of treatment for 41 clients, and at initial intake, again after a 6‐week no‐treatment waiting list period, and again at the termination of treatment, for 14 clients. Statistically and clinically significant improvements in SCL‐90‐R scores were obtained following counseling for those receiving immediate treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 12 publications
0
31
0
2
Order By: Relevance
“…Another limitation could be related to the fact that the sample investigated in the present study is mainly composed of females; however, this gender difference in requesting psychological help is well known and has already been documented in previous studies regarding the university counselling services (Connell et al, 2008;Hogg & Deffenbacher, 1988;Minami et al, 2009;Talley & Clack, 2006;Vonk & Thyer, 1999).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Another limitation could be related to the fact that the sample investigated in the present study is mainly composed of females; however, this gender difference in requesting psychological help is well known and has already been documented in previous studies regarding the university counselling services (Connell et al, 2008;Hogg & Deffenbacher, 1988;Minami et al, 2009;Talley & Clack, 2006;Vonk & Thyer, 1999).…”
Section: Discussionmentioning
confidence: 88%
“…The first review examining the effectiveness of student counselling was published by Breakwell in 1987, summarising the works carried out between 1966 and 1986. Later, other works investigated the effectiveness of student counselling services in the Anglo-Saxon area (Connell, Barkham, & Mellor-Clark, 2008;Hogg & Deffenbacher, 1988;Minami et al, 2009;Talley & Clack, 2006;Vonk & Thyer, 1999). One of the main concerns regarding these studies is that they were conducted outside Italy, thus reducing the possibility of making their results generally applicable to the country (Connell, Barkham, Cahill, Gilbody, & Madill, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Turner et al (1996) found that time-limited counselling had a modest impact on adjustment in a sample of student clients. Vonk & Thyer (1999), in a study of the effectiveness of short-term counselling (average 10 sessions), found that, compared to students in a waiting-list condition, those who received counselling recorded substantial levels of clinical improvement. In this study, 73 % of clients met the criteria for psychiatric 'caseness' at intake.…”
Section: College and Student Counsellingmentioning
confidence: 99%
“…Itwasjustificationally concluded that "It is clear that the project was successful in accomplishing the objectives of moving a significant number of children out of foster home placement" (Stein & Gambrill, 1977, p. 509; see also Stein, Gambrill, & Wiltse, 1978). I note that this study did not involve a placebo control group, a failing it shares with much applied research involving real life clients in agency-based settings (e.g., Baker & Thyer, 2000;Vonk & Thyer, 1999).…”
Section: On the Relative Value Of Positive And Negative Knowledgementioning
confidence: 99%
“…But I did not use Baker and Thyer (2000) as an example of an atheoretical intervention. Similarly, the reader can review what I said about the Vonk and Thyer (1999) study. I said that·the practitioners used many diverse approaches to intervention .…”
Section: On Atheoretical Interventionsmentioning
confidence: 99%